[177Lu]Lu-PSMA-617 Salivary Gland Uptake Characterized by Quantitative In Vitro Autoradiography - Roswitha Tönnesmann; Philipp T. Meyer; Matthias Eder; Ann-Christin Baranski (MDPI AG, 2019)
Irradiation of salivary glands remains the main dose-limiting side effect of therapeutic PSMA-inhibitors, especially when using alpha emitters. Thus, further advances in radiopharmaceutical design and therapy strategies are needed to reduce salivary gland uptake, thereby allowing the administration of higher doses and potentially resulting in improved response rates and better tumor control. As the uptake mechanism remains unknown, this work investigates the salivary gland uptake of [177Lu]Lu-PSMA-617 by autoradiography studies on pig salivary gland tissue and on PSMA-overexpressing LNCaP cell membrane pellets. Displacement studies were performed with non-labeled PSMA-617 and 2-PMPA, respectively. The uptake of [177Lu]Lu-PSMA-617 in glandular areas was determined to be partly PSMA-specific, with a high non-specific uptake fraction. The study emphasizes that [177Lu]Lu-PSMA-617 accumulation in pig salivary glands can be attributed to a combination of both specific and non-specific uptake mechanisms. The observation is of high impact for future design of novel radiopharmaceuticals addressing the dose-limiting salivary gland irradiation of current alpha endoradiotherapy in prostate cancer.